A phosphoinositide-mediated switch of GET pathway receptor dimerization in Arabidopsis - Lei Zhang; Aron Struß; Miaojing Qin; Annika Dombrowski; Tingting Li; Stefanie Viebahn; Dietmar Mehlhorn; Christopher Grefen (Proceedings of the National Academy of Sciences, 2025)
The Guided Entry of Tail-Anchored Proteins (GET) pathway facilitates the insertion of tail-anchored (TA) proteins into the ER membrane, but its regulation in plants remains unclear. In Arabidopsis , we identify phosphatidylinositol 4-phosphate (PI4P) as an anchor that brings the receptors At GET1 and At GET2 into proximity within the ER membrane. At GET2 binds PI4P via an arginine residue in its transmembrane domain. Mutation of this residue disrupts At GET1 and At GET2 proximity at the ER, impairing GET complex function. This defect can be rescued by synthetic dimerization of A tGET1 and At GET2. The PI4P phosphatase RHD4 acts as a gatekeeper, converting PI4P to PI and enabling At GET1– At GET2 interaction, which influences TA protein insertion and root hair growth. Our findings establish the PI4P-RHD4 module as a crucial regulator of GET receptor dynamics, highlighting the interplay between phospholipids and protein trafficking in plants.